What I learned and what I learnt : teaching English while honoring language and culture at a predominantly Black institution - Williams, Concetta A., 1976-; Magras, Lydia Brown, 1948- (Critical black pedagogy in education., 2019)
Research and practical experiences suggest that African American students' achievement continues to be affected where they are likely to be taught by faculty who have limited experience with the nuances of African American Vernacular English. This book offers a resource for teaching speakers of AAVE at the post-secondary level.